The Concept of at-Ta’wid in the Development of Students’ Personality: An Ibn Miskawayh Perspective - Maisa Hurul Aeni; Mizani Khairul Sya’ad; Nuur Alfi Laelah (Institut KH Ahmad Sanusi (INKHAS) Sukabumi, 2026)
This study is motivated by the weakening of character formation among students, indicated by declining moral values, discipline, and responsibility in educational environments. The study aims to analyze the concept of At-Ta’wid (habituation) in shaping students' personality based on Ibn Miskawaih’s perspective and its relevance in modern education. This study’s novelty lies in integrating Ibn Miskawaih’s classical framework with modern learning theories to build a comprehensive habituation model. This research uses a qualitative library research method. Primary data include Ibn Miskawaih’s works, supplemented by relevant journals and books. Data were collected through documentation and analyzed using content analysis. The findings show that At-Ta’wid is an effective method for character formation through continuous and consistent habituation. Repeated positive behaviors gradually form stable character traits in students. The success of habituation is influenced by teachers' role modeling and a supportive environment. The study concludes that At-Ta’wid remains highly relevant in modern education as a strategy for developing students' personality and moral character.